2011
DOI: 10.1007/s12237-011-9444-0
|View full text |Cite
|
Sign up to set email alerts
|

Selenium Behavior in San Francisco Bay Sediments

Abstract: Sediment and porewater samples (1997-1999) were collected in the Northern Reach of the San Francisco Bay and Sacramento-San Joaquin Delta for determinations of sedimentary selenium and its chemical speciation. Total sedimentary selenium increased with depth, with approximately 50% of the sedimentary selenium as elemental selenium and 35% as organic selenide. Porewater total dissolved selenium increased with depth in the estuary and Delta, and fluxes out of the sediments were calculated at 0.01 and 0.06 nmol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 55 publications
(112 reference statements)
0
6
0
Order By: Relevance
“…The long residence time, high nutrient inputs, and deposition of fine-grained sediments allow some degree of oxygen-depletion in the sediments, especially in the sub-surface (Crauder and others, 2016). This could also affect Se transformation (Luoma and Presser, 2009) and speciation on suspended particulate material and in sediments (Meseck and Cutter, 2012). Because these processes vary in intensity and length from year to year, seasonal cycles in Se concentrations and bioavailability are expected to be complex.…”
Section: Influence Of Ecosystem Characteristics On Seleniummentioning
confidence: 99%
See 2 more Smart Citations
“…The long residence time, high nutrient inputs, and deposition of fine-grained sediments allow some degree of oxygen-depletion in the sediments, especially in the sub-surface (Crauder and others, 2016). This could also affect Se transformation (Luoma and Presser, 2009) and speciation on suspended particulate material and in sediments (Meseck and Cutter, 2012). Because these processes vary in intensity and length from year to year, seasonal cycles in Se concentrations and bioavailability are expected to be complex.…”
Section: Influence Of Ecosystem Characteristics On Seleniummentioning
confidence: 99%
“…Numerous studies over the last three decades have shown that sieved surface sediments at the Palo Alto mudflat reflect exposure of local organisms to contaminants released from local facilities and runoff (Thomson and others, 1984;Cain and Luoma, 1990). Additionally, Meseck and Cutter (2012) define the upper 2-cm of sediments in San Francisco Bay as the "re-suspended layer of sediments". Waves driven by the persistent afternoon winds in South Bay, and currents associated with the tides stir surficial sediments into the water-column on a near-daily basis (Thomson and others, 1984;Meseck and Cutter 2012).…”
Section: Selenium Concentrations In South Bay Sedimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The vertical diffusional flux of dissolved selenium from the bottom sediment was estimated using a modified form of Fick's first law (Meseck & Cutter 2012): (1) where J is the diffusional flux, θ is the porosity, m has a value of 3 for surface sediments (Ullman & Aller 1982) ) (Meseck & Cutter 2012), and ΔSe/Δz is the observed concentration gradient of porewater selenium. The selenium concentration at z = 0 m (Se 0 ) in water from the near-bottom of the core was used as the initial point in the concentration gradient.…”
Section: Flux Estimatesmentioning
confidence: 99%
“…However, the exchange of DISe flux (0.002 ± 0.0004%) between the sediment and the water column was negligible compared with other sources. The sediment−water exchange of selenium is also a negligible source in San Francisco Bay, as indicated by stable isotope ratios (Johnson et al 2000) and sediment porewater values (Me seck & Cutter 2012). The net transport of DISe from Sanggou Bay to the Yellow Sea accounted for 10 ± 3% of the DISe export.…”
Section: Selenium Budget For Sanggou Baymentioning
confidence: 99%